Assessment of Stress Corrosion Cracking on Pipeline Steels Weldments Used in the Petroleum Industry by Slow Strain Rate Tests - Contreras, A.; Salazar, M.; Albiter, A.; Galván, R.; Vega, O. (IntechOpen, 2011)
None